Chronic loose stools following right‐sided hemicolectomy for colon cancer and the association with bile acid malabsorption and small intestinal bacterial overgrowth - Larsen, Helene Mathilde; Krogh, Klaus; Borre, Mette; Gregersen, Tine; Mejlby Hansen, Mette; Arveschoug, Anne K; Christensen, Peter; Drewes, Asbjørn Mohr; Emmertsen, Katrine Jøssing; Laurberg, Søren; Ladefoged Fassov, Janne (Colorectal disease, 2023)
Aim Patients treated with right‐sided hemicolectomy for colon cancer may suffer from long‐term bowel dysfunction, including loose stools, urgency and faecal incontinence. The underlying causes are poorly understood. The aim of this case–control study was to investigate the aetiology of chronic loose stools among patients with right‐sided hemicolectomy curatively operated for cancer. Method Cases with chronic loose stools (Bristol stool type 6–7) after right‐sided hemicolectomy were compared with a control group of patients with right‐sided hemicolectomy without loose stools. All patients underwent a selenium‐75 homocholic acid taurine (SeHCAT) scan to diagnose bile acid malabsorption (BAM) and a glucose breath test to diagnose small intestinal bacterial overgrowth (SIBO). Gastrointestinal transit time (GITT) was assessed with radiopaque markers. In a subgroup of patients, fibroblast growth factor 19 (FGF19) was measured in fasting blood. SIBO was treated with antibiotics and BAM was treated with bile acid sequestrants. Results We included 45 cases and 19 controls. In the case group, 82% (n = 36) had BAM compared with 37% (n = 7) in the control group, p < 0.001. SIBO was diagnosed in 73% (n = 33) of cases with chronic loose stools and in 74% (n = 14) of controls, p = 0.977. No association between BAM and SIBO was observed. GITT was similar in cases and controls. No difference in median FGF19 was observed between cases and controls (p = 0.894), and no correlation was seen between FGF19 and SeHCAT retention (rs 0.20, p = 0.294). Bowel symptoms among cases were reduced after treatment. Conclusion BAM and SIBO are common in patients having undergone right‐sided hemicolectomy for cancer. Chronic loose stools were associated with BAM but not with SIBO.